2014
DOI: 10.1242/bio.20149613
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric inheritance of cytoophidia in Schizosaccharomyces pombe

Abstract: A general view is that Schizosaccharomyces pombe undergoes symmetric cell division with two daughter cells inheriting equal shares of the content from the mother cell. Here we show that CTP synthase, a metabolic enzyme responsible for the de novo synthesis of the nucleotide CTP, can form filamentous cytoophidia in the cytoplasm and nucleus of S. pombe cells. Surprisingly, we observe that both cytoplasmic and nuclear cytoophidia are asymmetrically inherited during cell division. Our time-lapse studies suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 28 publications
(34 reference statements)
1
67
0
1
Order By: Relevance
“…They also demonstrated that CTPS localizes to filamentary structures in Drosophila melanogaster and in rat hippocampal neurons (Noree et al 2010). Subsequent studies have shown that CTPS can also form filaments in human cells (Carcamo et al 2011, Chen et al 2011) and fission yeast (Zhang et al 2014). Thus, the cytoophidium represents a new type of intracellular compartment that is strikingly conserved across prokaryotes and eukaryotes (Liu 2011).…”
Section: Budding Yeastmentioning
confidence: 93%
See 4 more Smart Citations
“…They also demonstrated that CTPS localizes to filamentary structures in Drosophila melanogaster and in rat hippocampal neurons (Noree et al 2010). Subsequent studies have shown that CTPS can also form filaments in human cells (Carcamo et al 2011, Chen et al 2011) and fission yeast (Zhang et al 2014). Thus, the cytoophidium represents a new type of intracellular compartment that is strikingly conserved across prokaryotes and eukaryotes (Liu 2011).…”
Section: Budding Yeastmentioning
confidence: 93%
“…A eukaryotic cell might contain both cytoplasmic cytoophidia and nuclear cytoophidia (Carcamo et al 2014, Gou et al 2014, Shen et al 2016, Zhang et al 2014). If not specified, the term cytoophidia refers to cytoplasmic cytoophidia.…”
Section: Nomenclaturementioning
confidence: 99%
See 3 more Smart Citations